Actual goals and objectives of strategic development of domestic industry - Anatoliy A. Govorin; Andrey V. Kostin (Статистика и экономика)
The article justifies that in the conditions of stagnation in the Russian economy and the absence of prerequisites for its breakthrough development, it is necessary to seek new approaches in managing the development of economic systems.The purpose of this article is to set the correct goal for the development of the domestic industry and to justify the mechanism for achieving it. A new approach is proposed in managing the strategic development of industrial enterprises, aimed at long-term growth of the quality of their technologies. It is proved that the implementation of such a strategy provides a benchmark for a quantitative indicator of the quality of human-machine systems – the economic level of their technology.A number of methods for the strategic development of individual industrial enterprises and their systems based on economic and technological modeling of the development of industrial production are proposed. The tasks of managing the development of enterprises based on the criterion of maximizing their economic and technological quality and the need for state participation in the directed transformation of the country’s industrial complex are substantiated.The need to ensure the linkage of strategies for the development of industrial enterprises with the strategy for the development of the economy as a whole is stressed.